2007
DOI: 10.1111/j.1467-7687.2007.00631.x
|View full text |Cite
|
Sign up to set email alerts
|

The mirror neuron system: grasping others’ actions from birth?

Abstract: In the adult human brain, the presence of a system matching the observation and the execution of actions is well established. This mechanism is thought to rely primarily on the contribution of so-called 'mirror neurons', cells that are active when a specific gesture is executed as well as when it is seen or heard. Despite the wealth of evidence detailing the existence of a mirror neuron system (MNS) in the adult brain, little is known about its normal development. Yet, a better understanding of the MNS in infa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
137
3
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(149 citation statements)
references
References 100 publications
6
137
3
3
Order By: Relevance
“…Conflicting results in developmental psychology attribute either a developmental period to spatial cognition (Piaget). Besides, these results conflict with other researches in which infants do demonstrate good coordination and coherence across modalities (Gibsonian), even from restricted pre-natal experiences [1], [2].…”
contrasting
confidence: 55%
See 2 more Smart Citations
“…Conflicting results in developmental psychology attribute either a developmental period to spatial cognition (Piaget). Besides, these results conflict with other researches in which infants do demonstrate good coordination and coherence across modalities (Gibsonian), even from restricted pre-natal experiences [1], [2].…”
contrasting
confidence: 55%
“…Besides, these results conflit with other researches in which neonates do demonstrate coordination and coherence across modalities, even from restricted pre-natal experiences [1], [2]. Post-natal experiments done by Gibson, Spelke and Meltzoff (among other researchers) on intermodal matching argue for such a view [8], [9], [10].…”
Section: Introductioncontrasting
confidence: 44%
See 1 more Smart Citation
“…The intercommunication between specific brain regions, which are often referred to as mirror neuron system or action observation network, has been suggested to enable this inference of others' intentions and imitation of their behavior (Buccino et al, 2004;Craighero, 2004, 2005;Iacoboni, 2005Iacoboni, , 2009Iacoboni and Dapretto, 2006;Kilner et al, 2007). While a genetic predisposition may supply the foundation to develop such a system (Rizzolatti and Craighero, 2004;Ferrari et al, 2006;Lepage and Théoret, 2007;Bonini and Ferrari, 2011;Casile et al, 2011), its development -per se -seems to be strongly determined by social interaction (Meltzoff, 2007;Heyes, 2010;Nagai et al, 2011;Froese et al, 2012;Saby et al, 2012), sensorimotor experience, motor cognition, and embodiment (Gallese and Goldman, 1998;Catmur et al, 2007;Gallese, 2007a;Gallese et al, 2009). Due to observations such as the foregoing, cognitive science has recently undergone a pragmatic turn, focusing on the enactive roots of cognition (Engel et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, electroencephalographic (EEG) and neuroimaging research has revealed that the mirror neuron system may be functional during early infancy (Lepage & Théoret, 2007;Marshall & Meltzoff, 2011;Shimada & Hiraki, 2006). Indeed, Shimada and Hiraki (2006) used near-infrared spectroscopy (NIRS) to show that 6-monthold infants activated the primary motor regions when observing another person's actions.…”
Section: Introductionmentioning
confidence: 99%